2015
DOI: 10.1002/cmdc.201500441
|View full text |Cite
|
Sign up to set email alerts
|

High‐Throughput Screening (HTS) by NMR Guided Identification of Novel Agents Targeting the Protein Docking Domain of YopH

Abstract: Recently we described a novel approach, named HTS by NMR that allows the identification, from large combinatorial peptide libraries, of potent and selective peptide mimetics against a given target. Here we deployed the HTS by NMR approach for the design of novel peptoid sequences targeting the amino terminal domain of the Yersinia outer protein H (YopH-NT). We aimed at disrupting the protein-protein interactions between YopH-NT and its cellular substrates, with the goal of inhibiting indirectly YopH enzymatic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
28
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 45 publications
4
28
0
Order By: Relevance
“…As additional attempt to derive novel CD44 binding agents, we also carried out a screening campaign using the HTS by NMR approach [29, 31] . Hence, we prepared and tested 76 mixtures of a tetra-peptide combinatorial library composed by 19 natural amino acids (the 20 natural amino acids except cysteine) as building blocks [31a] .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As additional attempt to derive novel CD44 binding agents, we also carried out a screening campaign using the HTS by NMR approach [29, 31] . Hence, we prepared and tested 76 mixtures of a tetra-peptide combinatorial library composed by 19 natural amino acids (the 20 natural amino acids except cysteine) as building blocks [31a] .…”
Section: Resultsmentioning
confidence: 99%
“…Hence, we prepared and tested 76 mixtures of a tetra-peptide combinatorial library composed by 19 natural amino acids (the 20 natural amino acids except cysteine) as building blocks [31a] . In addition, we also prepared and tested a tri-peptide combinatorial library (see Methods).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…189 In times of recurring endemic outbreaks and an increasing awareness of potential bioterroristic attacks, YopH lately became a highly studied target for the treatment of especially Y. pestis infections through small molecule inhibitors of YopH. [190][191][192][193] Finally, recent data showed that -at least in pathogenic E. coli -bacterial proteins involved in the regulation of virulence, including type III secretion, are also activated by tyrosine phosphorylation -a mechanism that was long believed to be completely absent in bacteria. 194 Whether YopH might thus also play a regulatory role within the bacterial cell is an exciting topic for future research.…”
Section: Structure and Functionmentioning
confidence: 99%